A new forestry bacterial isolate Brevundimonas sp. negatively affecting on Caenorhabditis elegans - Son, Le Tho; Thi Thu, Nguyen (Academia Journal of Biology, 2025)
Bacteria are food sources for the Caenorhabditis nematodes. This interaction becomes a model to understand the effects of bacteria on the nematodes and other host organisms. In this research, we report the identification of the environmental Brevundimonas sp. CFBb114 in Cat Tien National Park with the 16S rDNA. CFBb114 inhabits within the microhabitats of the nematode genus Caenorhabditis. We fed Caenorhabditis elegans with CFBb114 to investigate the effects of CFBb114 on C. elegans, and found that the bacteria reduced longevity and reproduction and changed the behavior of C. elegans. This research will facilitate the study of how host organisms evolve mechanisms against the impacts of bacteria.